Staphylococcus aureus nt5 gene mutation through CRISPR RNA-guided base editing weakens bacterial virulence and immune evasion - Xinpeng Liu; Lan Huang; Yang Ye; Haiyi Wang; Min Tang; Fuqiang He; Zijing Xia; Shi Deng; Peng Zhang; Ruiwu Dai; Shufang Liang (Virulence)
The resistance of commonly used clinical antibiotics, such as daptomycin (DAP), has become increasingly serious in the fight against Staphylococcus aureus (S. aureus) infection. It is essential to explore key pathogenicity-driven genes/proteins in bacterial infection and antibiotics resistance, which contributes to develop novel therapeutic strategies against S. aureus infections. The nt5 gene of S. aureus, encoding 5’-nucleotidase (NT5), is nearly unknown for its function in drug resistance and bacterial infection. Herein, to reveal nt5 gene role in drug resistance and infection ability of S. aureus, we performed nt5C166T gene mutation using a clustered regulatory interspaced short palindromic repeat ribonucleic acid (RNA)-guided base editing system to investigate the lose-of-function of NT5 protein. Subsequent transcriptome sequencing of the mutant strain revealed that nt5 inactivation caused changes in cell membrane integrity and inhibited nucleotide metabolism, suggesting the nt5 gene may be involved in bacterial drug resistance and virulence. The mutant strain exhibited enhanced tolerance to DAP treatment by attenuating cell membrane potential dissipation and slowing deoxyribonucleic acid release. Moreover, the nt5 mutation alleviated abscess degree of mouse kidneys caused by S. aureus infection byreducing the expression of IL-1β, IL-6, and IL-18. The nt5 mutant strain was easily swallowed by host immune cells, resulting in weak bacterial toxicity of the S. aureus mutant in the bacterial infection process. In summary, nt5 gene mutation confers tolerance to DAP and a lower bacterial capacity to form kidney abscesses through phagocytosis of host immune cells, which indicates the targeted inhibition of NT5 protein would offer a potential new therapeutic strategy against S. aureus infection.